Perancangan Sistem Informasi Monitoring Inventaris Dan Pengadaan Aset Pada Kantor Kecamatan Paal Merah Kota Jambi Berbasis Web - Febrina Mardayani, Risa; Alam Jusia, Pareza; Setiawan, Roby (LPPM STIKOM Dinamika Bangsa, 2025)
The Paal Merah District Office of Jambi City is located at Jl. Sultan Syahril RT.16 Talang Bakung Village, Jambi City. In the data processing process using Microsoft Excel, but there are still many obstacles in data processing, such as the difficulty of recording Inventory Monitoring and Asset Procurement data, planning previously planned activities because the data search process is slow, data does not appear automatically so that it must be input repeatedly, and data cannot be integrated because there is no database. The purpose of this study was to analyze the current system, in order to overcome the problems faced at the Paal Merah District Office of Jambi City, by designing a Web-based Information System for Monitoring Inventory and Procurement of Assets at the Paal Merah District Office of Jambi City. The stages that will be carried out in solving the problems discussed are, identifying, searching for information based on theoretical foundations, collecting data using observation and interview methods, analyzing to find solutions to the problems faced by the Paal Merah District Office of Jambi City. The system development method uses a waterfall model, the implementation of this research uses the PHP Program Language and MySQL DBMS, to produce data processing applications that are expected to facilitate data processing and report generation.